Influence of surfactants on bioleaching of arsenic-containing gold concentrate - Fang, Fang; Zhong, Hong; Jiang, Fang-ming; Li, Zhao-hui; Chen, Yong-fa; Zhan, Xue-hui (Journal of Central South University, 2014)
To shorten the bioleaching cycle of arsenic-containing gold concentrate, surfactants were used to promote the interaction between bacteria and ore to increase the arsenic leaching rate. Three different kinds of surfactants were used to evaluate the effects of surfactants on the growth of bacteria and arsenic leaching rate of arsenic-containing gold concentrate. The mechanism underlying surfactant enhancement was also studied. Results show that when relatively low-concentration surfactants are added to the medium, no significant difference is observed in the growth and Fe 2+ oxidation ability of the bacteria compared with no surfactant in the medium. However, only the anionic surfactant calcium lignosulfonate and the nonionic surfactant Tween 80 are found to improve the arsenic leaching rates. Their optimum mass concentrations are 30 and 80 mg/L, respectively. At such optimum mass concentrations, the arsenic leaching rates are approximately 13.7% and 9.1% higher than those without the addition of surfactant, respectively. Mechanism research reveals that adding the anionic surfactant calcium lignosulfonate improves the percentage of bacterial adhesion on the mineral surface and decreases the surface tension in the leaching solution.